Spontaneous resorption of sub-retinal cortical lens material - Gadkari, Salil S (Medknow Publications & Media Pvt Ltd, 2014)
We report a rare case of retained sub-retinal cortical material, which underwent spontaneous resorption. Patient presented with a left eye traumatic retinal detachment with a large retinal tear and posteriorly dislocated cataractous lens. Vitrectomy, lensectomy, silicone oil injection, and endolaser were performed. A good visual result was achieved. The report draws attention to this condition and highlights possible technique for minimizing risk of this complication in similar cases.